Publicandum (s.n., 1797)
Wyznaczenie ścisłych terminów zmiany służby
Not. rkps.: ``Exempl. für Richtowo''
Keywords: Prawodawstwo; Prusy; Polska; Służba prawodawstwo 18 w. Prusy; Służba prawodawstwo 18 w. Polska